PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS UNTUK MENINGKATKAN HASIL BELAJAR FIKIH SISWA KELAS VII MTS NEGERI LUWU UTARA KAB LUWU UTARA - RAMLAH RAMLAH (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2021)
This research is motivated by the importance of teachers in choosing the right learning model, so that learning is as active as possible involving students, so students can build their own knowledge in a fun learning that leads to increased learning outcomes. The main objective of this research is to find out whether by applying the Student Team Achievement Divisions (STAD) cooperative learning model, it can improve the fiqh learning outcomes of seventh grade students of MTs Negeri Luwu Utara. This research was carried out in class VII MTs Negeri Luwu Utara starting in the second week of September until the first week of October 2020 (first semester). The number of students involved was 69 people, which were divided into 10 working groups. Observations were carried out in two cycles, where each cycle consisted of a preparation (planning) stage, action implementation, observation and evaluation, reflection, and action revision. Data analysis was carried out descriptively, by displaying it in the form of tables, histograms and equipped with percentage calculations. The results showed that student learning completeness in the first cycle was 69.44% and in the second cycle was 91.67%. Thus, there is an increase in mastery learning outcomes from cycle I to cycle II by 22.23%. It was also found that in the first cycle the number of groups who completed 12.5% ??increased by 50.0% to 62.5% in the second cycle. The conclusion of this study is that the application of the Student Team Achievement Divisions (STAD) type of cooperative learning model can improve Fiqh learning outcomes for seventh grade students of MTs Negeri Luwu Utara. It is recommended that Fiqh teachers consider the use of the Student Team Achievement Divisions (STAD) cooperative learning model, and it is also recommended that further research be conducted to see how student learning outcomes are if group members are not permanent. ABSTRAKPenelitian ini dilatar-belakangi oleh pentingnya guru dalam memilih model pembelajaran yang tepat, agar pembelajaran itu sebanyak mungkin melibatkan siswa secara aktif, sehingga siswa dapat membangun pengetahuannya sendiri dalam sebuah pembelajaran yang menyenangkan yang berujung pada peningkatan hasil belajar. Tujuan utama penelitan ini adalah untuk mengetahui apakah dengan menerapkan model pembelajaran kooperatif tipe Student Team Achievement Divisions (STAD) dapat meningkatkan hasil belajar Fikih siswa kelas VII MTs Negeri Luwu Utara. Penelitian ini dilaksanakan di kelas VII MTs Negeri Luwu Utara yang dimulai pada pekan ke II bulan September sampai dengan pekan ke 1 Oktober 2020 (semester I) . Jumlah siswa yang terlibat sebanyak 69 orang , yang dibagi dalam 10 kelompok kerja. Observasi dilaksanakan selama dua siklus, dimana masing-masing siklus terdiri atas tahap persiapan (perencanaan), pelaksanaan tindakan, observasi dan evaluasi, refleksi, dan revisi tindakan. Analisis data dilakukan secara deskriptif, dengan menampilkannya dalam bentuk tabel, histogram dan dilengkapi dengan perhitungan persentase. Hasil penelitian menunjukan bahwa, ketuntasan belajar siswa pada siklus I sebesar 69,44% dan pada siklus II sebesar 91,67%. Dengan demikian ada peningkatan ketuntasan hasil belajar dari siklus I ke siklus II sebesar 22,23%. Didapatkan juga bahwa pada siklus I jumlah kelompok yang tuntas sebesar 12,5 % meningkat sebesar 50,0% menjadi 62,5% pada siklus kedua. Kesimpulan penelitian ini adalah bahwa penerapan model pembelajaran kooperatif tipe Student Team Achievement Divisions (STAD) dapat meningkatkan hasil belajar Fikih siswa kelas VII MTs Negeri Luwu Utara. Disarankan agar guru-guru mata pelajaran Fikih mempertimbangkan penggunaan model pembelajaran kooperatif tipe Student Team Achievement Divisions (STAD), dan juga disarankan ada penelitian lanjutan untuk melihat bagaimana hasil belajar siswa jika anggota kelompok tidak permanen.